Stability analysis of linear impulsive differential systems under structural perturbation - Martynyuk, A.A.; Stavroulakis, I.P. (Український математичний журнал, 1999)
The stability and asymptotic stability of solutions of large-scale linear impulsive systems under structural perturbations are investigated. Sufficient conditions for stability and instability are formulated in terms of the fixed signs of special matrices. Досліджуються стійкість та асимптотична стійкість розв'язків великомасштабної лінійної імпульсної системи при структурних збуреннях. Достатні умови стійкості та нестійкості сформульовані на основі знаковизначеності спеціальних матриць